Muscle function during cross-country skiing at different speed and incline conditions - Werkhausen, A.; Lundervold, A.; Gløersen, Ø. (Journal of Experimental Biology, 2023)
The human musculoskeletal system is well adapted to use energy-efficient muscle-tendon mechanics during walking and running, but muscle behaviour during on-snow locomotion is unknown. Here, we examined muscle and muscle-tendon unit behaviour during diagonal-style cross-country roller skiing at three speed and incline conditions to examine whether skiers can exploit energy-saving mechanisms of the muscle-tendon unit. We assessed lower leg muscle and muscle-tendon unit mechanics and muscle activity in 13 high-level skiers during treadmill roller skiing using synchronised ultrasound, motion capture, electromyography and ski-binding force measurements. Participants skied using diagonal style at 2.5 and 3.5 m s-1 up 5 deg, and at 2.5 m s-1 up 10 deg. We found an uncoupling of muscle and joint behaviour during most parts of the propulsive kick phase in all conditions (P<0.01). Gastrocnemius muscle fascicles actively shortened ~0.9 cm during the kick phase, while the muscle-tendon unit went through a stretch-shortening cycle. Peak muscle-tendon unit shortening velocity was 5 times faster than fascicle velocity (37.5 versus 7.4 cm s-1, P<0.01). Steeper incline skiing was achieved by greater muscle activity (24%, P=0.04) and slower fascicle shortening velocity (3.4 versus 4.5 cm s-1, P<0.01). Faster speed was achieved by greater peak muscle activity (23%, P<0.01) and no change in fascicle shortening velocity. Our data show that, during diagonal-style cross-county skiing, muscle behaviour is uncoupled from the joint movement, which enables beneficial contractile conditions and energy utilisation with different slopes and speeds. Active preloading at the end of the glide phase may facilitate these mechanisms.